Simplify each expression. (giving 50 points and brainliest)
1. -[-(11-22)]
2.
[tex]( \frac{3}{2} ) \times ( - \frac{22}{33)} [/tex]

3.
[tex] \frac{ {4}^{2} }{ {5}^{2} } [/tex]

4.
[tex] - \frac{4}{3} - \frac{4}{13} [/tex]

5.
[tex] \sqrt{ \frac{27}{3} } [/tex]​

Respuesta :

Answer:

See below

Step-by-step explanation:

[tex]-[-(11-22)]=-[-(-11)]=-[11]= \large\boxed{-11}[/tex]

[tex]$ \left( \frac{3}{2} \right) \cdot \left(-\frac{22}{33} \right) = -\frac{66}{66}=\large\boxed{-1} $[/tex]

[tex]$\frac{4^2}{5^2}=\large\boxed{\frac{16}{25}} $[/tex]

[tex]$-\frac{4}{3} -\frac{4}{13} = -\frac{4 \cdot 13}{3 \cdot 13} -\frac{4 \cdot 3}{13 \cdot 3} = -\frac{52}{39} -\frac{12}{39} = \large\boxed{-\frac{64}{39}} $[/tex]

[tex]$\sqrt{\frac{27}{3} } =\sqrt{9} =\large\boxed{3}$[/tex]